Investigation of Mathematics Problems Placed in Children’s Periodicals - Okay, Şirin; İnci̇kabi, Lütfi (Çanakkale Onsekiz Mart Üniversitesi, 2019)
The aim of this study was to analyse the mathematicalcontents of Bilim Çocuk and TSE Öncü Çocuk periodicals in terms of the physicalcharacteristics of the magazines, the compatibility with the curriculum and thecharacteristics of the problems. Being qualitative in nature, document analysiswas used to analyse the problems in the children’s periodicals. In the scope ofthe research, 202 issues of Bilim Çocuk, and 74 issues of TSE Öncü Çocuk wereinspected and the mathematical content pages were compiled. According to thefindings of the research, the mathematical content in the periodicalscorresponded to 4% of the total pages. It was determined that more than half ofthe mathematical content in the magazines (63%) was of the problem type, 29% wasplanned as play activities and only 8% was mathematical articles. It was notedthat the majority of the images used in the magazines (63%) are suitable forthe content. When reviewing the contents of the periodicals, problem-solvingskills seemed to come to the forefront of the skills involved. In addition, it wasnoticed that in children's magazines, the problems of daily life were givenless emphasis than the problems not related to daily life. Moreover, problemsolving abilities were found to be the most needed dimension.

Buçalışmanın amacı, geçmişten günümüze yayımlanan Bilim Çocuk ve TSE Öncü Çocukdergilerinin matematik içeriklerini dergilerin fiziksel özellikleri, ilgilimüfredatla uyumu ve yer verilen problemlerin karakteristikleri bağlamındaanaliz etmektir. Nitel doğaya sahip bu çalışmada problemlerin analizinde dokümananalizi kullanılmıştır. Araştırma kapsamında Bilim Çocuk Dergisi’nin 202sayısı, TSE Öncü Çocuk Dergisi’nin 74 sayısı taranmış, matematiksel içeriktespit edilen sayfaları derlenmiştir. Araştırmanın bulgularına göre, dergilerdematematiksel içeriğe ayrılan alan toplam sayfaların %4’üne karşılıkgelmektedir. Dergilerdeki matematiksel içeriğin yarıdan fazlasının (%63)problem türü etkinliklerde olduğu, %29’unun oyun olarak planlandığı ve sadece%8 matematiksel makale şeklinde olduğu belirlenmiştir. Dergilerde kullanılangörsellerin çoğunluğunun (%63) içeriğe uygun görseller olduğu fark edilmektedir.Dergilerdeki içerik incelendiğinde problem çözme becerilerinin yer verilenbeceriler arasında ön plana çıktığı görülmektedir. Çocuk dergilerinde günlükyaşam problemlerine günlük yaşamla ilgili olmayan problemlere oranla daha azyer verildiği fark edilmiştir. Ayrıca problem çözme yetisi, en fazla ihtiyaçduyulan gereklilik boyutu olarak göze çarpmıştır.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; Children periodicals; mathematics education; problem specifications; Matematik eğitimi; problem özellikleri; süreli çocuk yayınları; 4. Education